Covid-19 Outbreak and New Normal Teaching in Higher Education: Empirical Resolve from Islamic Universities in Indonesia - Cahyadi, Ani (Dinamika Ilmu, 2020)
Mid of March 2020, the coronavirus 19 pandemic outbreaks caused many offices, markets, schools, and universities closed to maintain its dead spreading. It makes all the offline activities should be changed into online interaction including at higher education. Lawrence & Tar (2018) reflected a study about factors that influence teachers’ adoption and integration of ICT in teaching/learning process. This study is about the activity of new normal in conducting online education relating to the use of six strategies applied which are applied by teachers in the Islamic University of Antasari Banjarmasin Indonesia. Within the new normal period, this study reveals the six strategies on conducting online education namely; a) the strategy of contextualization, b) the strategy of proper delivery, c) the strategy of high adaptation on using technology, d) the strategy of adequate support, e) the strategy of quality participation, f) the strategy of sustainable processes.